THE INFLUENCE OF PRICE AND SOCIAL MEDIA PROMOTION FACEBOOK MARKETING ON PURCHASE DECISIONS FOR AM CLOTHING DISTROS IN BREBES - Yuni Indayani; Hendri Sucipto (Salwatuna, 2022)
Abstract The purpose of the study was to determine and determine the effect of price and social mediaadvertisingonpurchasingdecisionsforAmClothBrebesdistribution.consideringthenumberofdistributions in Brebes, the approach used in this study is an associative approach. The population in thisstudy is infinity, with accidental sampling technique, so that a sample of 65 people was taken, the type ofdatacollectedtosupportthevariableswithaquestionnaire,thedataanalysistechniqueinthisstudyused,includedinstrumentaltest,validityandreliability,classicalassumptiontestincludednormality,multicollinearity,heteroscedasticity,multiplelinearregressionanalysis,ttestFtest,dataprocessingusingSPSSsoftwareprogram(statusticpackageforthesocialscienceb)0.25forwindows,theresultsofthestudyshow that partially, each price and promotion variable influence on purchasing decisions of Am ClothDistrosinBrebes,priceandpromotionvariablesaffectpurchasingdecisionsofAmClothDistrosinBrebes